Malaysian research-support librarians’ self-directed learning traits: Examining demographic differences and their relationship with competencies - A Samah, Nazrinda; Mohd Tahir, Lokman; Wan Mamat, Wan Ali @ Wan Yusoff; Talib, Rohaya; Abdul Latif, Adibah (SAGE Publications, 2021)
Research-support librarians have to play an effective role in supporting learning, providing services and anticipating the requirements of academic researchers. However, previous studies revealed that these librarians lacked the competencies to keep abreast of new resources, services and technologies. Although there is a large body of literature discussing the comprehensive competencies required of research-support librarians, very few have attempted to investigate this issue in the Malaysian context. Based on this situation, this study attempts to investigate the self-directed learning traits and competencies of research-support librarians in Malaysian public universities. This study also aims to identify the influence of self-directed learning on competencies. A total of 215 research support librarians from Malaysian public universities were selected. The findings revealed that the competencies of these librarians are still at medium level. The most noticeable and lowest competency was in information technology skills, followed by research and contributions to the profession and library management. The most prevalent competencies were interpersonal skills, followed by information literacy, entrepreneurialism, foundational knowledge and collections development.